2020
DOI: 10.3390/pharmaceutics12090894
|View full text |Cite
|
Sign up to set email alerts
|

Can Implementation of Genetics and Pharmacogenomics Improve Treatment of Chronic Low Back Pain?

Abstract: Etiology of back pain is multifactorial and not completely understood, and for the majority of people who suffer from chronic low back pain (cLBP), the precise cause cannot be determined. We know that back pain is somewhat heritable, chronic pain more so than acute. The aim of this review is to compile the genes identified by numerous genetic association studies of chronic pain conditions, focusing on cLBP specifically. Higher-order neurologic processes involved in pain maintenance and generation may explain g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 128 publications
(158 reference statements)
0
4
0
Order By: Relevance
“…It is defined as CLBP without a definite and recognizable primary disease, persisting for at least three months with clinical signs of muscle tension or stiffness localized below the costal margin of the spine and above the inferior gluteal folds in the presence or absence of sciatica [1]. The impact of NSCLBP on individuals and society is enormous because studies showed that it results in significant health burden, disability, absence from work, high cost of management, reduced quality of life, and increased psychological variables of anxiety with dissatisfaction and hopelessness [1][2][3][4].…”
Section: Research Paper Effects Of Lumbar Stabilization and Graded Ac...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is defined as CLBP without a definite and recognizable primary disease, persisting for at least three months with clinical signs of muscle tension or stiffness localized below the costal margin of the spine and above the inferior gluteal folds in the presence or absence of sciatica [1]. The impact of NSCLBP on individuals and society is enormous because studies showed that it results in significant health burden, disability, absence from work, high cost of management, reduced quality of life, and increased psychological variables of anxiety with dissatisfaction and hopelessness [1][2][3][4].…”
Section: Research Paper Effects Of Lumbar Stabilization and Graded Ac...mentioning
confidence: 99%
“…However, further studies on LSE and GAE in patients with NSCLBP are necessary because reports implicate numerous biochemical mediators in patients with NSCLBP [12][13][14]. Emerging evidence of pain mechanisms in NSCLBP suggests the need to profile biochemical mediators of pain for optimum intervention [3,12]. Biochemically, the pain response is associated with the presence of inflammatory mediators of bradykinin, serotonin, histamine, adenosine triphosphate, prostaglandins, nitric oxides, cytokines, leukotrienes, cyclooxygenases, and neurotrophins [15].…”
Section: Research Paper Effects Of Lumbar Stabilization and Graded Ac...mentioning
confidence: 99%
“…Low back pain (LBP) has a lifetime prevalence as high as 84% and poses a significant burden to society 1 . Despite its frequency, the etiology of LBP is not well understood: only 10% of low back pain is attributed to a specific pathology, such as nerve root compression, fracture, tumor, spondylolisthesis, or stenosis 2,3 . The remaining cases are labeled under the umbrella term non-specific low back pain, which is commonly treated by addressing the symptoms instead of the causal mechanisms of LBP 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In their review, Suntsov et al discuss how an individual’s genotype could affect their response to therapy, as well as how genetic polymorphisms in CYP450 and other enzymes are crucial for affecting the metabolic profile of drugs used for the treatment of chronic lower back pain. They suggest that implementation of gene-focused pharmacotherapy has the potential to deliver select, more efficacious drugs and avoid unnecessary polypharmacy-related adverse events in many painful conditions [ 11 ]. Buendia et al report on the clinical value of PGx in special populations such as children undergoing liver transplantation.…”
mentioning
confidence: 99%